Nanotechnology Development for Formulating Essential Oils in Wound Dressing Materials to Promote the Wound-Healing Process: A Review - Ilenia De Luca; Parisa Pedram; Arash Moeini; Pierfrancesco Cerruti; Gianfranco Peluso; Anna Di Salle; Natalie Germann (Applied Sciences, 2021)
Wound healing refers to the replacement of damaged tissue through strongly coordinated cellular events. The patient’s condition and different types of wounds complicate the already intricate healing process. Conventional wound dressing materials seem to be insufficient to facilitate and support this mechanism. Nanotechnology could provide the physicochemical properties and specific biological responses needed to promote the healing process. For nanoparticulate dressing design, growing interest has focused on natural biopolymers due to their biocompatibility and good adaptability to technological needs. Polysaccharides are the most common natural biopolymers used for wound-healing materials. In particular, alginate and chitosan polymers exhibit intrinsic antibacterial and anti-inflammatory effects, useful for guaranteeing efficient treatment. Recent studies highlight that several natural plant-derived molecules can influence healing stages. In particular, essential oils show excellent antibacterial, antifungal, antioxidant, and anti-inflammatory properties that can be amplified by combining them with nanotechnological strategies. This review summarizes recent studies concerning essential oils as active secondary compounds in polysaccharide-based wound dressings.